A salvage pathway maintains highly functional respiratory complex I - Karolina Szczepanowska (Nature Portfolio, 2020)
Maintenance and quality control of the mitochondrial respiratory chain complexes responsible for bulk energy production are unclear. Here, the authors show that the mitochondrial protease ClpXP is required for the rapid turnover of the core N-module of respiratory complex I, which happens independently of other modules in the complex.